Confiabilidade de instrumento para avaliar a satisfação com a Educação Permanente em Saúde na Estratégia Saúde da Família (IAEPS-ESF) - Pereira, Elainey de Albuquerque Tenorio (2018)
The Family Health Strategy (ESF) aims to promote health through the performance of multiprofessional teams in the improvement of health determinants and determinants. The Permanent Education in Health (EPS) in the ESF aims to improve the process of qualification of health professionals and practices by bringing the knowledge of daily practice with a view to achieving improved access and quality of the AB, consolidating it as a reorientadora of the Health Care Model in Brazil. However, the FHS requires reliable instruments to evaluate the professionals' satisfaction with EPS. In this sense, the objective of this study was to determine the reliability of the psychometric instrument for evaluation of EPS satisfaction in the Family Health Strategy (IAEPS-ESF). This is a methodological study with a cross-sectional design and quantitative analysis carried out in the city of Maceio (AL). IAEPS-ESF was applied to the professionals of the ESF teams from May 2017 to March 2018. The IAEPS-ESF was elaborated by the team of the Commission for Integration Teaching- Service (CIES) of the state of Alagoas based on the instrument Self ‒ Assessment for Improving Access and Quality of Primary Care of the Ministry of Health ‒ AMAQ ‒ AB. The data were consolidated in an online form (Google Forms), obtaining the database in Excel Table and analyzed in the software Statistical Package for Social Sciences (SPSSR) for Windows version 22 (SPSS Inc., Chicago, IL, USA). The sample consisted of 304 ESF professionals randomly and proportionaly drawn in the eight Health Districts of the Municipality of Maceio (AL). The IAEPS-ESF presented a good internal consistency standard, with a general value of 0.876 for the Cronbach alpha, its reliability being validated. It is recommended to modify the item "Teams use education devices and distance matrix support for the qualification of the care provided to users" in sub-dimension 3 ‒ Permanent Education and Qualification of Health Care Teams, as it was observed improvement of alpha of Cronbach of the sub-dimension with its removal (Cronbach alpha after removal of the item = 0.741). It is expected that the IAEPS-ESF can contribute to the evaluation of the satisfaction of the EPS, helping in the elaboration of in-service training strategies under the SUS.